2020
DOI: 10.1111/bjso.12371
|View full text |Cite
|
Sign up to set email alerts
|

Are women more likely to wear red and pink at peak fertility? What about on cold days? Conceptual, close, and extended replications with novel clothing colour measures

Abstract: Evolutionarily minded researchers have hypothesized that women advertise their ovulatory status by wearing red or pink clothing on relatively cold days. Many of these studies have been based on samples of women who have self-reported their clothing choices, a practice that raises questions about accuracy. In two studies, we evaluated the relationship between women's fertility and their clothing choices using four methods for measuring clothing colour: self-reports; trained raters' judgements of garment colorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
(165 reference statements)
2
3
1
Order By: Relevance
“…However, the effect of wearing more sexy clothes in the luteal phase is in the opposite direction as expected and was not supported by hormonal associations. While the reported null findings are in line with other studies (Arslan et al, 2021; Blake, Bastian, et al, 2017; Hone & McCullough, 2020; Schleifenbaum et al, 2021), they need replication given the limitations of Study 1: First, poor inter‐coder reliabilities for some dimensions suggest that they were very hard to detect based on the photographs, and that the measures were thus not reliable (e.g. wearing high heels).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, the effect of wearing more sexy clothes in the luteal phase is in the opposite direction as expected and was not supported by hormonal associations. While the reported null findings are in line with other studies (Arslan et al, 2021; Blake, Bastian, et al, 2017; Hone & McCullough, 2020; Schleifenbaum et al, 2021), they need replication given the limitations of Study 1: First, poor inter‐coder reliabilities for some dimensions suggest that they were very hard to detect based on the photographs, and that the measures were thus not reliable (e.g. wearing high heels).…”
Section: Discussionsupporting
confidence: 91%
“…While the null results of wearing red clothes are in line with results of Study 1 and previous studies (Blake,Dixson,10 Please note that eyeglasses were coded as 1 = yes and 2 = no. Hone & McCullough, 2020), this study did not replicate that women show less skin when fertile, as reported in Study 1. Neither did it replicate previous studies reporting that women wear sexier or more skin revealing clothes when fertile (in line with Arslan et al, 2021).…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations